PELAKSANAAN LARANGAN PEMILIKAN TANAH PERTANIAN YANG BERADA DI LUAR KECAMATAN (ABSENTEE) PADA DAERAH PEMEKARAN (SUATU STUDI PADA KANTOR PERTANAHAN KABUPATEN LABUHANBATU) - SRI ELPINA NAINGGOLAN (PREMISE LAW JURNAL, 2017)
Land is God’s blessing. Based on the right of control of the State, it is the Government’s obligation to carry out land registration throughout the Indonesian territory. UUPA (the Land Act) is intended to protect land and to organize land rights by giving land certificates as the evidence of the land ownership. UUPA attempted to minimize them by regulating the their limitation under Article 7, Article 10, and Article 17 which are the core of Land-reform. The principle of Land-reform is explained in Law No. 56 Prp/1950 on the specification of agricultural land area, and Article 3, paragraph (1) of PP No. 24/1961 in conjunction with PP No. 41/1964 on the Implementation of Land Distribution and Compensation.The research used juridical normative and descriptive analytic method in which the problems were solved by gathering and analyzing the data systematically. Primary data were obtained from the Subdistrict Heads of Silangkitang and Kota Pinang and from the staffs of the Land Office of Labuhanbatu Regency. Secondary data were obtained from primary, secondary, and tertiary legal materials, library research, field research, and interviews. The gathered data were analyzed qualitatively.The conclusion of the research was that the implementation of the prohibition to own land outside subdistrict (absentee) in Labuhanbatu Selatan Regency was the tenure of agricultural land outside subdistrict so that the extension did not have any effect on anything since the extension was concerned with Labuhanbatu Regency, while absentee land tenure was only in subdistrict.Keywords: Prohibition to Own, Absentee Land, Extension Area